Evaluation of volatile aldehydes as discriminating parameters in quality vinegars with protected European geographical indication. (10th November 2014) - Durán‐Guerrero, Enrique; Chinnici, Fabio; Natali, Nadia; Riponi, Claudio
Abstract BACKGROUND Thirty‐six high‐quality vinegars with geographical indication belonging to Sherry and Modena areas (vinegars of Jerez, balsamic vinegars of Modena and traditional balsamic vinegars of Modena) with all possible aging periods were analyzed to determine the content of volatile aldehydes. A solid‐phase extraction method with in‐cartridge derivatization using O‐(2, 3, 4, 5, 6‐pentafluorobenzyl)hydroxylamine followed by gas chromatography–mass spectrometry was employed. RESULTS Twenty‐two volatile aldehydes were identified and determined in the samples. Analysis of variance provided significant differences among the samples as a function of the type of vinegar, aging time and raw material. Principal component analysis and linear discriminant analysis demonstrated the possibility of discriminating the samples in terms of aging time and raw material. Linear aldehydes and compounds such as furfural, methional, nonenal, hexenal, 2‐methylbutanal and i‐butyraldehyde were the most significant variables able to discriminate the samples. CONCLUSION Aldehyde content of premium quality vinegars is a function of both ageing time and raw material. Their evaluation could be a useful tool with a view to ascertaining vinegar origin and genuineness. © 2014 Society of Chemical Industry